Petrophysical Properties and Reservoir Assessment of Mishrif Formation in Eridu oil field, Southern Iraq - Al-Mashhdani , Mohammed A. Jawad; Al-Zaidy, Aiad Ali Hussien (Iraqi Journal of Science, 2023)
This study is achieved in the local area of the Eridu oil field, where the Mishrif Formation is considered the main productive reservoir. The Mishrif Formation was deposited during the Cretaceous period in the secondary sedimentary cycle (Cenomanian-Early Turonian as a part of the Wasia Group, a carbonate succession widespread throughout the Arabian Plate.     The Mishrif Formation already have been evaluated in terms of depositional environments and their diagenetic processes. Here, it will test the previous conclusions with petrophysical properties delineated by using well logging. The results show there is a fully matching with two reservoir units (MA and MB). Dissolution and primary porosity are responsible for forming a variety of large porosity types. These porosity types have preserved the hydrocarbons in commercial quantities. MA and MB reservoir units show low gamma ray and high to moderate total and effective porosities values. The water saturation Sw in the upper unit (MA) is very high in generally to become water-bearing zone. This appears in all studied wells except in the E-NE part, characterized by patches area of moderate water saturation. In contrast, the lower unit (MB) is characterized by high values of hydrocarbon saturation (Sh) except for some areas in the middle of the studied field.      Cap rocks (CR1 and CR2) represents rock unit with low porosity and permeability due to the main components of these units. It contains lime mudstone with log response of this cap rocks indicates high gamma-ray peak value. Compaction and dolomitization are responsible for low porosity and permeability in this type of rock unit.